The research on cycloastragenol in the treatment of brain metastases from lung cancer: mechanistic exploration of radiotherapy sensitization and amelioration of brain injury - Yanyan Tao; Jingwen Chang; Jingwen Chang; Xinyi Zhu; Xinyi Zhu; Jingjing Han; Jingjing Han; Xinru Wang; Xinru Wang; Yun Sheng; Yun Sheng; Ziyi Sun; et al. (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to investigate the radiosensitizing and toxicity-reducing effects of Cycloastragenol (CAG) in the radiotherapy of lung cancer brain metastases.MethodsA brain metastasis model of lung cancer was established using stereotactic brain localization. After successful modeling, varying doses of CAG (5 mg/kg, 10 mg/kg, 20 mg/kg) were administered via intraperitoneal injection to evaluate its antitumor efficacy. Radiotherapy (3 Gy per session, total 10 sessions) was combined with CAG (20 mg/kg) to assess its radiosensitizing effects. Small-animal in vivo imaging was employed to evaluate antitumor efficacy and radiosensitization. Cognitive changes in mice were assessed using the novel object recognition test and the cylinder test. Neuroinflammatory responses in brain tissues were detected via immunofluorescence and qPCR. Transcriptome sequencing and network pharmacology were utilized to identify potential targets and mechanisms, while molecular docking validated interactions between CAG and key targets. Both in vitro and in vivo studies were conducted to elucidate the mechanisms underlying CAG’s adjuvant effects in radiotherapy, including enhancing efficacy and mitigating toxicity.Results1. CAG significantly suppressed the growth of Lewis lung carcinoma (LLC) brain xenografts. 2. CAG markedly enhanced the radiotherapeutic efficacy against lung cancer brain metastases. 3. CAG ameliorated radiation-induced brain injury in tumor-bearing mice by attenuating pro-inflammatory polarization of microglia/macrophages. 4. CAG inhibited the activity of the JAK/STAT signaling pathway in LLC brain tumor tissues, thereby downregulating the expression of neutrophil chemotaxis-associated cytokines, including CXCL3 and CCL5. 5. CAG alleviated radiation-induced brain injury in tumor-bearing mice by suppressing the IKK/NF-κB signaling pathway in LLC brain tumor tissues, which further modulated microglial/macrophage pro-inflammatory polarization.ConclusionCAG ameliorates neuroinflammation, enhances the therapeutic efficacy of radiotherapy for lung cancer brain metastases, and mitigates radiation-induced brain tumor injury by suppressing the activity of the JAK/STAT and IKK/NF-κB signaling pathways within metastatic lesions.